Біоіндикаційне картографування техногенно трансформованих територій м. Києва - Стець, Галина; Волошина, Наталія; Stets, Galyna; Voloshyna, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2016)
Уперше розглянуто питання біоіндикаційного картографування еколого-паразитологічного стану техно-генно трансформованих територій. Описано та апробовано методику створення картосхем місцевості щодо паразитарного забруднення на території міста Києва. The article investigated actual questions the lack of developed methods bioindication mapping of technogenic transformed territories, including periodic fixing state of widespread biological objects by morphological characters and mapping geometric elements, which determine the state of the environment; as a biological object was used zoonotic geohelminthes domestic carnivores (dogs) Toxocara canis, which is recorded in soil samples and using a marking point is applied to the card, constitute environmental schematic maps areas. We tested the adequacy of the method for example Kyiv. The positive effect is that the proposed method enables a differentiated test contamination of soil by toxocara. Using the method will more accurately identify the contamination zone by toxocara, assess and constant monitoring of technogenic transformed territories, to assess the level of contamination, control and plan human activities in the area.
Bioindicative Mapping of Technogenic Transformed Territories of Kiev.
Keywords: біоіндикаційне картографування; Toxocara canis; техногенно трансформовані території; еколого-паразитологічний стан; bioindication mapping; technologically transformed territories; ecological and parasitological state